Polimorfisme Protein Darah Ayam Kedu Jengger Merah dan Jengger Hitam di Satuan Kerja Non Ruminansia Temanggung - Sutopo Sutopo; Edy Kurnianto; Bagus Praditya Setyo Nugroho (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2016)
The objectives of this study were to determine the blood protein diversity first generation of Kedu chickens (G0)at Satuan Kerja Non Ruminansia Maron, Temanggung. The materials used in this study were each of 14 red andblack comb Kedu chickens. The methods of this study were observational and electrophoresis PAGE(Polyacrylamid Gel Electrophoresis). The observed parameters were loci of pre albumin (Palb), albumin (Alb),ceruloplasmin (Cp), transferrin (Tf), post transferrin (Ptf) and amylase-I (Amy-I). Gene structures were observedto characterize genetic diversity. Characterization of genetic diversity based on individual heterozygosity, meanheterozygosity and chi-square values for testing Hardy Weinberg equilibrium for each observed loci. The resultsshowed that red comb Kedu chickens had the highest gene frequencies of pre albumin, ceruloplasmin, transferrin,post transferrin and amylase-I those were 0,714; 0,714; 0,643; 0,643 and 0,536 respectively. The highestindividual heterozygosity of red comb Kedu chickens found in amylase-I (0,497) and also post transferrin (0,500),and amylase-I (0,500) for black comb Kedu chickens. The highest mean heterozygosity was found in black combKedu chickens (0,458). The chi-square calculation showed that the whole loci were at Hardy Weinbergequilibrium except pre albumin at red comb Kedu chickens.